(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
In this text we provide a meeting between Ignacio Martín-Baró’s liberation psychology and behavior analysis of J. G. Holland and B. F Skinner in order to list some affinities approaching these two psychologies. We argue, then, that such affinities represent an irresistible incentive to develop the scenario of a remarkable psychological revolution, as well as to consider the possibility that it will collaborate to emancipate the Latin American people (from their oppressors) and people (control of the elites). At this time, we allude to the atmosphere of uncertainty surrounding this lancinating phrase: “We do not know the agony we enter is that of the birth or death of humanity”. And we reflect, with a healthy dose of skepticism, but also of hope, that perhaps still we have the possibility to lighten our psychological praxis to cooperate with the agony of birth of humanity.